EXPLORING PHILIPPINE ENGLISH IN STUDENT PUBLICATIONS: PERSPECTIVES OF ENGLISH TEACHERS ON LANGUAGE USAGE AND ACCEPTANCE - Flores, Rogela Alcantara (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
The study used a quantitative descriptive research method to investigate the use of lexical features of PE in news articles of student publication. A content analysis of 31 news articles identified 38 instances of Philippine English, categorized into coinages (24), preservation of items infrequent or lost in other varieties (5), normal expansions (5), and borrowings (4). Questionnaires were administered to 21 English teachers to assess the acceptability of these terms. The majority of the Philippine English lexical features found in the student publication were widely accepted by the English teachers. The results showed that terms such as “Fab Lab” and “U-Days” were widely accepted (100%), while others such as “blastful” and “sophomostrial” met with high rejection rates (90.5% and 100%, respectively). The study recommends inclusive language teaching practices that reflect the linguistic diversity of the Philippines. This study not only contributes to the understanding of PE but also provides practical implications for language teaching and curriculum development.